PERANCANGAN SISTEM INFORMASI TRACKING PROGRESS KOLABORATIF DALAM PENGELOLAAN MEDIA PADA DISKOMINFO BANYUWANGI - Ummi Fadlilatuz Zakiyah; Zaehol Fatah; Lutfiyatul F Anas (CV. Denasya Smart Publisher, 2025)
The design of a collaborative progress tracking information system is used for media management at the Office of Communication, Informatics, and Encryption (Diskominfo) in Banyuwangi Regency. Public information management faces complex challenges, especially in coordination among teams, utilization of technology, and efficient information distribution. Diskominfo Banyuwangi experiences significant obstacles in the media management process involving various parties, such as admins, staff, and partners, often operating separately and lacking integration, which leads to miscommunication, delays in revisions, and suboptimal content distribution. The need for an integrated information system has become urgent to support real-time team collaboration and ensure orderly and transparent work progress documentation. To address the issues of coordination and tracking of work, support from an information system is needed, which can facilitate collaboration among teams, ease the documentation of work activities, and accelerate the process of revision and publication of content. Overall, this design is expected to serve as a foundation for the development of an information system that supports more effective, adaptive, and integrated technology-based public services